Implementation of Islamic Entrepreneurship Concept in Double Track SMA Program - Anik Yulikah; M. Arif Faizin; Agus Eko Sujianto (Cahaya Abadi Publisher, 2022)
This study aims to find a solution in reducing unemployment in Indonesia, especially educated unemployment through an entrepreneurial program, namely the double track high school program by implementing the concept of Islamic entrepreneurship. The method in this study uses a descriptive field research method with a qualitative approach and the type of multi-site research, while the data analysis used is interactive analysis. This study took the research location at SMAN 1 Bendungan and SMAN 1 Tugu, Trenggalek Regency. The result of this study is the discovery of elements of the concept of Islamic entrepreneurship that are applied in the double track high school program, such as the concept of income distribution with the sharing movement while promoting (BSP), the concept of sincerity in work and business with various demands for innovation and achievement, and the concept of earnestness in work and business. halal haram with interest-free capital program (MTB). By applying the concept of Islamic entrepreneurship in doing business, business is not only oriented to worldly material but also connected and oriented to the hereafter.